(untitled) (Dhaka University Journal of Biological Sciences, 2017)
The effect of different phytoplankton species on growth, survival and fatty acids composition of Nile tilapia (Oreochromis niloticus) was evaluated for 24 weeks. Treatment-1 was fed with commercial feed as Control, treatment-2 was fed with Spirulina platensis, treatment-3 was fed with Chlorella vulgaris and treatment-4 was fed with mixed phytoplankton (Chlorella vulgaris, Spirulina platensis, Azolla pinnata and Pistia stratiotes). The condition factor of fish found in treatment-3 with Chlorella vulgaris (1.73 ± 0.02) was significantly higher than that of treatment-1 as control (1.56 ± 0.02) at 24 weeks culture period. The specific growth rate of treatment-4 with mixed phytoplankton diet (2.00 ± 0.10) was significantly higher than treatment-3 with Chlorella vulgaris (1.13 ± 0.05) after 24 weeks of rearing. There was no significant difference among the four treatments in case of average daily gain, feed conversion ration and survival rate. The use of different phytoplankton such as Spirulina platensis, Chlorella vulgaris and Azolla pinnata influence the fatty acid profiles of Nile tilapia. Findings also showed that the amount of eicosapentaenoic acid (EPA) in treatment-3 fed with Chlorella vulgaris (1.83 ± 0.22) was highly significant than the other treatments. The highest amount of docosahexaenoic acid (DHA) was found in treatment-1 fed with commercial feed (2.70 ± 0.53%) and lowest in treatment-2 with Spirulina platensis (0.06 ± 0.02%). Among 19 unsaturated fatty acid, the highest concentration of PUFAs were recorded in treatment-3 (42.55 ± 3.46%) fed with Chlorella vulgaris. The findings of this study suggest that raising Nile tilapia with Chlorella vulgaris and Spirulina platensis in ponds may improve the growth and fatty acid profile of the fish. Dhaka Univ. J. Biol. Sci. 26(1): 13-27, 2017 (January)